Evaluation of Ability to Pay and Willingness to Pay Kualanamu Airport Railink User Service - Deci Rianta Br Sebayang; Hera Widyastuti (Institut Teknologi Sepuluh Nopember (ITS), 2024)
Kualanamu Airport railway transportation has yet to become the public's leading choice for commuting to Kualanamu Airport because, according to the public, the rates set are still relatively expensive. So, further research is needed on the level of passenger satisfaction, ability to pay (ATP), and willingness to pay (WTP) so that tariffs can be determined according to people's ability and willingness to pay. The method used in this research includes distributing questionnaires and interviews using stated preference techniques. The methods used in this research are the importance-performance analysis (IPA) method and the household budget method. The main priority for the level of satisfaction that needs to be improved is the attribute in quadrant 1 (A), namely the time interval between Kualanamu Airport train, Kualanamu Airport train operational schedules, and Kualanamu Airport train ticket prices. The ability to pay (ATP) for train users at Kualanamu Airport is IDR 79,000. Willingness to pay (WTP) from Kualanamu Airport train users is IDR 49,000.